2009
DOI: 10.1051/forest/2009061
|View full text |Cite
|
Sign up to set email alerts
|

Fall fertilization of Pinus resinosa seedlings: nutrient uptake, cold hardiness, and morphological development

Abstract: Abstract• Fall fertilization may increase plant nutrient reserves, yet associated impacts on seedling cold hardiness are relatively unexplored.• Bareroot red pine (Pinus resinosa Ait.) seedlings in north-central Minnesota, USA were fall fertilized at the end of the first growing season with ammonium nitrate (NH 4 NO 3 ) at 0, 11, 22, 44, or 89 kg N ha −1 . Seedling morphology and cold hardiness [assessed by freeze induced electrolyte leakage (FIEL)] were evaluated six weeks after fertilization and following th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
34
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(39 citation statements)
references
References 27 publications
(38 reference statements)
4
34
1
Order By: Relevance
“…Consequently, proper seedling nutrition at the nursery is a critical cultural practice for subsequent field performance (Birchler et al 2001). If nutrient uptake is limited in the nursey without supplemental fertilization, biomass accumulation during hardening may lead to an internal nutrient dilution (Boivin et al 2004); nutrient dilution can be averted by applying fertilizer in the fall (Boivin et al 2002, Islam et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Consequently, proper seedling nutrition at the nursery is a critical cultural practice for subsequent field performance (Birchler et al 2001). If nutrient uptake is limited in the nursey without supplemental fertilization, biomass accumulation during hardening may lead to an internal nutrient dilution (Boivin et al 2004); nutrient dilution can be averted by applying fertilizer in the fall (Boivin et al 2002, Islam et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, greater height growth increment was detected at the high N rate, similar to findings with Pinus resinosa Ait. (Islam et al 2009) and Larix olgensis (Li et al 2012), but in contrast to Pinus elliottii var. elliottii and Pinus taeda in which heights were not affected by fall fertilization (Sung et al 1997, Irwin et al 1998, VanderSchaaf & McNabb 2004.…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 97%
“…elliottii and Pinus taeda in which heights were not affected by fall fertilization (Sung et al 1997, Irwin et al 1998, VanderSchaaf & McNabb 2004. Islam et al (2009) seedlings demonstrated that fall fertilization of Pinus resinosa resulted in a swollen terminal bud (i.e., 9 mm vs. 18 mm for non-fertilized and fertilized seedlings, respectively).…”
Section: Iforest -Biogeosciences and Forestrymentioning
confidence: 99%
See 2 more Smart Citations